New Trends in Mechanism and Machine Science Theory and Industrial Applications - Wenger, Philippe; Flores, Paulo (Mechanisms and Machine Science,, 2017)
This book collects the most recent advances in mechanism science and machine theory with application to engineering. It contains selected peer-reviewed papers of the sixth International Conference on Mechanism Science, held in Nantes, France, 20-23 September 2016, covering topics on mechanism design and synthesis, mechanics of robots, mechanism analysis, parallel manipulators, tensegrity mechanisms, cable mechanisms, control issues in mechanical systems, history of mechanisms, mechanisms for biomechanics and surgery and industrial and nonindustrial applications.